Efektivitas Kinerja Pegawai Dalam Penggunaan Sistem Kearsipan Berbasis Elektronik (Studi Pada PT Perusahaan Listrik Negara (Persero) Unit Induk Transmisi Jawa Bagian Timur dan Bali) - Nani Septiana; Sugeng; Windi Ikhsa Velani (Jurnal Manajemen DIVERSIFIKASI, 2024)
Performance of effectiveness is the ability to succeed in a work carried out by workers in producing something expected, and choosing the right goals to achieve the set goals. Performance of effectiveness can increase if a person has the skills and expertises in accordance with the demands of the work. The effectiveness of an employee's performance has several indicators as a guide to measure the level of success towards the effectiveness of employee performance. This research was aimed to explain the effectiveness of employee performance on the electronic-based filing system in the office of PT Perusahaan Listrik Negara (Persero) Transmission Main Unit, Eastern Java and Bali. This study utilized qualitative research, where its explained the effectiveness of employee’s performance. The data were collected through observation, interviews and documentation. Data analysis techniques applied in this study ere information gathering, data reduction, data presentation, and final conclusions. Data validation techniques in this study were source triangulation, technical triangulation, and time triangulation. The results of this study indicated that the effectiveness of employee work in the use of an electronic-based filing system in the office of PT Perusahaan Listrik Negara (Persero) Transmission Main Unit, Eastern Java and Bali. (1) the ability to adapt to the employees at this stage, employees of the PT Perusahaan Listrik Negara (Persero) Main Unit Transmission Office for Eastern Java and Bali are already able to adapt in designing change management strategies, understand the technology and are able to conduct ongoing training, it was demonstrated by several informant exposure. (2) employee performance, at this stage the employees of PT Perusahaan Listrik Negara (Persero) Main Transmission Unit for Eastern Java and Bali have been able to improve their skills or skills by participating in several activities and ongoing training according to their field of work, then employees are able to increase their job loyalty so as to obtain maximum results, as well as improve work discipline. (3) Employee job satisfaction in this stage the employees of the PT Perusahaan Listrik Negara (Persero) Main Unit Transmission Office for Eastern Java and Bali have achieved job satisfaction by providing a good work environment, and supported by supporting facilities so as to provide morale to employees. PT Perusahaan Listrik Negara (Persero) Transmission Main Unit for Eastern Java and Bali in supporting the effectiveness of employee performance by providing full support to all of its employee bureaucracy both structurally and functionally. Keywords: Effectiveness, Performance, Electronic Based